STUDIES ON THE ENHANCEMENT OF LIPID PRODUCTION IN Chlorella pyrenoidosa - POOJA SHARMA; M.B. KHETMALAS; G.D.TANDON (International Journal of Pharma and Bio Sciences, 2014)
Microalgae are emerging as the sustainable key source of green fuels and neutraceuticals. In the current study, a strain of Chlorella pyrenoidosa was isolated, identified and biochemically analyzed. Studies were undertaken to enhance its biomass and lipid productivities for sustainable biodiesel production. Growth was monitored in BG-11, BBM, Bristol and Fogg’s medium as cell count, O.D, PCV and dry cell weight measurements. BG-11was found to be the most suitable medium. Specific growth rate was determined to be 10.64 mg/l/d in 25 days with a lipid productivity of 29.26 mg/l/d. Nitrogen stress was introduced by varying concentration of major nitrogen source in the BG-11 medium. Varied inorganic nitrogen source like urea, ammonium nitrate and ammonium sulphate had a significant effect on biomass and lipid productivities of algae. Ammonium nitrate enhanced the lipid production leading to a three fold increase in its yield. Growth rate was accelerated by 15.3 % with the supply of 5 % carbon dioxide.